Between capture and discretion - The determinants of distressed bank treatment and expected government support - Magdalena Ignatowski; Josef Korte; Charlotte Werger (European Central Bank (ECB), 2015)
In this paper, we analyze how sources of political influence relate to the actual regulatory treatment of distressed banks and to the expectation of bank support provided by the government. We assemble a unique dataset that links U.S. banks' sources of influence (e.g., lobbying expenditures, proximity to the relevant legislative committee, prior affiliation with regulatory or government institutions) to bank financial data, actual bank supervisory actions, and market-inferred expected government support. Employing this novel data, we cast some light on how regulatory decision making is affected by these sources of influence. Our findings suggest that banks' influence matters for the regulatory treatment of distressed banks, as well as for the expectation of support regardless of bank distress. Several conditions increase the effectiveness of sources of influence in actual regulatory treatment: Lobbying activities are more effective with increasing lobbying expenditures, deteriorating capital ratios, and with the aid of former politicians.
Keywords: D72; G21; G28; 330; bank regulation; bank sources of influence; lobbying; Prompt Corrective Action; regulatory discretion